Brebes Sheep Skin That is Hydrolyzed With Excess Acid Solution (CH3COOH) and Sitrate Acid (C6H8O7) Became Gelatin - Muhamad Hasdar; Wadli Wadli; Daryono Daryono (Program Studi Peternakan, Fakultas Pertanian, Universitas Veteran Bangun Nusantara, 2019)
Local resources from Brebes Regency that have not been maximized properly are sheep skin. Brebes sheep skin can be converted into gelatin. This study aims to determine the quality of the yield and gelatin protein of sheep skin hydrolyzed using weak acids. The main ingredient of this research is sheep skin from Brebes Regency, which is 1-2 years old. The research method uses a completely randomized design (CRD) 2 x 3 factorial pattern where the first factor is the soaking material (CH3COOH 2% v / v and C6H8O7 2% v / v) and the second factor is the immersion time (2 hours, 3 hours and 4 hour), then proceed with the Real Difference test using the Duncan Multiple Range Test (DMRT). The yield measurement results showed the percentage of sheep skin gelatin is 10,12-10,77%, and the measurement of sheep skin gelatin protein showed a percentage of 70,96-72,87%. The ability of CH3COOH 2% in hydrolyzing sheep skin collagen is better than C6H8O7 2%. The highest percentage of yield and protein is at 4 hours soaking time for each type of solution.Keywords: Gelatin, Low Acid, protein, sheep skin, rendement